MANAJEMEN MEDIA POWER POINT UNTUK MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) (STUDI KASUS DI SMKN 1 TALAGA MAJALENGKA) - Andri Marta Sudirja; Andewi Suhartini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The background of this research is the problem of power point media management is one part of the problem of improving the quality of learning. The problems that occur in power point media management are not optimal planning, implementation, and assessment so that it has an impact on the quality of teachers and the quality of learning. The lack of success in power point media management is due to the less than optimal use of learning media implemented in each school that has not been managed optimally, the learning process has not reached the target effectively, the learning media has not been well managed, so that teachers have not been able to show the expected improvement in the quality of learning. The quality of education is something that must be considered and strived to achieve, because education will be in vain if the quality and graduates are low. It will be worse and worse if the educational output adds to the burden on the community, family and country. In general, the management of learning media at SMKN 1 Talaga Majalengka has not shown a satisfactory impact on improving the quality of teachers themselves, especially for students, this is influenced by many factors. Power point media management is still not optimal in improving the quality of learning. This research is a qualitative research which takes the background of power point media management to improve the quality of Islamic education learning at SMKN 1 Talaga Majalengka. Data collection was carried out by conducting observations, interviews, and documentation studies. Data analysis was carried out by giving meaning to the data that was collected, and from that meaning it was concluded. Checking the validity of the data was carried out using triangulation by means of check recheck and cross checking.